Coping Strategies in Liver Transplant Recipients and Caregivers According to Patient Posttraumatic Growth - Pérez-San-Gregorio, M. Ángeles; Martín-Rodríguez, Agustín; Borda-Mas, Mercedes; Avargues-Navarro, M. Luisa; Pérez-Bernal, José; Gómez-Bravo, M. Ángel (Frontiers in Psychology, 2017)
The purpose of this study was to analyze the differences in coping strategies employed by liver transplant recipients and their family members according to patient posttraumatic growth. Two matched groups of 214 liver transplant recipients and 214 family members were selected. The Posttraumatic Growth Inventory and Brief COPE were used. The most relevant results were: 1) Interactive effects in active coping, support (instrumental and emotional) and acceptance strategies, which were all used more by patients with higher growth levels, while their family members showed no differences in use of these strategies by patient growth level. Furthermore, while a low level of patient growth did not mark differences between them and their caregivers, a high level did, patients employing more active coping and support (instrumental and emotional), 2) In both groups a high level of patient growth was associated with more use of positive reframing and denial than a low one, and 3) Self-blame was employed by patients more than by their caregivers. It was concluded that a high level of posttraumatic growth in liver transplant recipients is associated with more use of healthy coping strategies, basically active coping, instrumental support, and emotional support.